THE TOXIC EFFECT OF NEEM EXTRACT, SPINOSAD AND ENDOSULFAN ON THE GROWTH OF APHIDS AND ITS PREDATOR - B. VIMALA; K. MURUGAN; M. DEECARAMAN; S. KARPAGAM; M. VIJAYALAKSHMI; K. SUJATHA (The Bioscan, 2010)
The present investigation was carried out to study the toxic effect of Neem seed kernel extract, spinosad and endosulfan comparitively. The chief volatile compound azardiractin present in Neem seed kernel extract appear to block the neurosecretory cells and resulting in disruption of development of eggs and preventing adult maturation. Spinosad reduces the moulting of larvae and pupae to adult, but it is less toxic than endosulfan. Our results clearly showed endosulfan contains highly toxic molecules when compare both natural (Neem) and bacterial (Spinosad). The present study positively suggests natural pesticide like neem extract is usually safe and beneficial for the environment.